Ecology and conservation of bottlenose dolphins in Madeira Archipelago, Portugal - Dinis, Ana Margarida Brites Caetano (2015)
This study aimed to provide an insight on the ecology of the bottlenose dolphin population in Madeira archipelago. To achieve this, population structure; group dynamics, site-fidelity, residency and movement patterns within and out of the study area; survival and abundance estimates and spatial and temporal distribution and habitat preferences related to physiographic parameters using data collected between 2001-2011, were investigated. Photo-identification data analysis revealed strong evidences that bottlenose dolphins seen in the archipelago of Madeira belong to an open population with regular recruitment of new animals to the area. This population exhibited a typical fission-fusion society, in which short-term acquaintances prevail, with only a few long-lasting associations. Photo-identification methods demonstrated that there is a large variability in residency pattern, with resident, transient and migrant individuals. Only a small number of dolphins were found to be resident (4.3%). Social network diagram as well as SLAR analysis supported the existence of a mixed population of residents, migrants and transients. Mark-recapture methods estimated a high survival rate, within the range of other long-lived cetacean species. The resident community is composed of app. 180 individuals. In addition, around 400 dolphins of different residency patterns were found to use the south area of Madeira Island. Spatial distribution indicated that bottlenose dolphins were regularly found in shallow and closer to shore areas, suggesting the existence of biological processes influenced by bathymetry. Moreover, temporal patterns revealed no strong seasonal fluctuation in the presence of bottlenose dolphins in Madeira archipelago waters. Bottlenose dolphins are listed under the Annex II of the EU habitats Directive that requires the designation of Special Areas of Conservation (SACs) for this species; as such, the knowledge gained through this work can be used by governmental authorities to the establishment and management of areas for the conservation of bottlenose dolphin in Madeira archipelago.